Maximum power limiting with average current mode control for photovoltaic system - Ray-Lee Lin; Li-Wei Yen (2010 IEEE Energy Conversion Congress and Exposition, 2010)
This paper presents a novel maximum power limiting (MPL) technology for the photovoltaic system. Most conventional MPPT technologies in the photovoltaic system are implemented with digital control circuit, which causes the cost-consuming issue. Therefore, the proposed MPL photovoltaic system can be implemented with analog control circuit, which is substituted for the digital control circuit. By associating the output characteristics of solar cell module, the proposed MPL control technology adjusts the photovoltaic current and power with average current-mode control (ACMC) scheme. Especially, this proposed MPL control scheme with the ACMC can be simply and cost-effectively implemented with the present power-factor-correction (PFC) control ICs available on the market. Furthermore, with considering the temperature effect on the electronic characteristics of the solar cell module, the temperature compensation circuit is associated with the MPL circuit to ensure the claimed function even at different temperature conditions. Finally, the prototype circuit of the 85W photovoltaic system with the proposed MPL control scheme is built in order to validate the claimed MPL function.